Enhanced Performance of Organic Solar Cells with Increased End Group Dipole Moment in Indacenodithieno[3, 2‐b]thiophene‐Based Molecules. (2nd July 2015) - Intemann, Jeremy J.; Yao, Kai; Ding, Feizhi; Xu, Yunxiang; Xin, Xukai; Li, Xiaosong; Jen, Alex K.‐Y.
Abstract : Four new molecular donors are reported using a D1‐A‐D2‐A‐D1 structure, where D1 is an oligiothiophene, A is a benzothiadiazole, and D2 is indacenodithieno[3, 2‐b]thiophene. The resulting materials provide efficiencies as high as 6.5% in organic solar cells, without the use of solvent additives or thermal/solvent annealing. A strong correlation between the end group (D1‐A) dipole moment and the fill factor (FF), mobility, and loss in the open‐circuit voltage ( V OC ) is observed. Indacenodithieno[3, 2‐b]thiophene‐fluorobenzothiadiazole‐terthiophene (IDTT‐FBT‐3T) possesses the largest end group dipole moment, and in turn, has the highest mobility, FF, and power conversion efficiency in devices. It also has a similarly high V OC (0.95 V) to the other materials (0.93–0.99 V), despite possessing a much higher highest occupied molecular orbital (HOMO) energy level. Abstract : Four new ladder‐type molecular donors are reported with varying end groups and their photovoltaic properties are explored. It is found that utilizing end groups with larger ground‐state dipole moments results in significantly enhanced fill factors and decreased voltage losses in devices.